Effect of DME addition on turbulent flame structure in lean premixed CH4/DME/air mixtures. (15th June 2021) - Lin, Wenjun; Wang, Jinhua; Mao, Runze; Zhang, Weijie; Xia, Hao; Zhang, Meng; Huang, Zuohua
Highlights: Coupling effects of differential diffusion and turbulence were studied for CH4 /DME/air turbulent lean premixed flame. We proved that the mean flame surface density at different height can qualitatively represent the local consumption speed. With the turbulence intensity increasing, DME addition seems to have minor effect on curvature. At thin reaction zone, the differential diffusion effect on the turbulent burning velocity is enhanced by turbulence. Abstract: An experimental study was conducted on DME addition to lean premixed CH4 /air Bunsen flame in order to investigate differential diffusion and turbulence effects on flame structure. Three DME volume fractions of 0, 20% and 50% were adopted in the presence of carefully controlled laminar burning velocity at a near-constant level to highlight the differential diffusion effects. By extracting the flame front from the OH-PLIF images, the flame front curvature, turbulent burning velocity and mean flame surface density were obtained and discussed. Results show that DME addition and turbulence will eventually make the curvature distribution more symmetrical. In addition with the turbulence intensity increasing, the DME addition seems to have minor effect on curvature. The turbulent burning velocity is decreased with DME addition, which is in agreement with earlier research results for Le > 1 mixtures. In this study, we prove that the mean flame surface density at different height can qualitatively represent the local consumption speed ( ST, LC ). DME addition only changes the ST, LC distribution structure of the flame, while turbulence not only changes the structure, but also increases the maximum ST, LC value. It is also found that the decrease of turbulent burning velocity ( ST, GC ), caused by DME addition at low turbulence intensity, is mainly manifested by an increase of the flame height. Moreover at thin reaction zone, the interaction between turbulence and differential diffusion effect promotes the change of ST, LC distribution. Therefore, the effect of differential diffusion on ST, GC is enhanced by turbulence as the diffusion layer is broadened.